Behavior of Metallic Foam under Shock Wave Loading - Zoran Ren (Metals, 2012)
In this manuscript, the behavior of metallic foam under impact loading and shock wave propagation has been observed. The goal of this research was to investigate the material and structural properties of submerged open-cell aluminum foam under impact loading conditions with particular interest in shock wave propagation and its effects on cellular material deformation. For this purpose experimental tests and dynamic computational simulations of aluminum foam specimens inside a water tank subjected to explosive charge have been performed. Comparison of the results shows a good correlation between the experimental and simulation results.